Morphometries and aspects of bio-ecology of ephestia cautella (lepidoptera: pyralidae) on stored date fruit (phoenix Dactylifera) and hermetic control technique (2011)
Rate of fecundity, life cycle, morphometic characteristics of Ephestia cautella and control were investigated. These were done on sterilized dried date (Phoenix dactylifera) as substrate. Mean daily fecundity of 17 eggs was recorded, while a total of 1117 eggs were laid by 15 adults female E.cautella within 6 days of oviposition in perforated date. In another separate setup the life cycle from egg to adult took 37 ± 1.92 days, under a temperature and relative humidity of 32.5 ± 1 °C and 70 ± 5% respectively. First filial generation (F1) of 1, 217 adults emerged after 30 days of culture using two pairs of E.cautella, from this Fl, 54.7% and 45.3%, were males and females respectively. The morphometric characteristics of E.cautella revealed that female and male adult mean total body length ranges between 8.2 - 10.00mm and 7.9 - 8.9 mm respectively. The control set up on larval stage using varied poly then bag layers of three, two, and one layer with thickness of 0.056mm confirmed that three bags layers was the best treatment. Recorded percentage mortality values of 74.20%, 19.36% and 0.26% were obtained respectively from the set up.